2004
DOI: 10.1002/biof.552210164
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative activity of animal and vegetable dietary fibers

Abstract: Some dietary fibers originated from insects such as silkworm (Sericin) and others along with constituents of several representative seaweeds such as wakame Undaria pinnatifida; hijiki Hizikia fusifome; and kombu Laminaria japonica, were found to have fairly large reaction rates determined by quenching experiments of emission spectra in the near-infrared region lambdamax 1270 nm for singlet oxygen 1O2, Cypridina luminescence method for superoxide, and peroxide value (POV) for autoxidation. The determined reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Michel et al (1996) reported that the characteristic fermentation pattern associated with the fiber from the three brown algae they investigated was attributable to the peculiar fermentation of alginates, and mannuronate was shown not to be directly involved. As for the relationship of seaweed consumption to carcinogenesis, several reports have shown preventive effects of seaweeds against colorectal carcinogenesis in epidemiological studies (Tokudome et al, 1991;Hoshiyama et al, 1993), or in experimental studies in rats (Yamamoto and Maruyama, 1985;Teas et al, 1998); proposed mechanisms for such effects include inhibition of reactive oxygen species (Maruyama et al, 2003;Suzuki et al, 2004), or the modulation of natural killer cell activity (Teas, 1983). Furthermore, there are several reports regarding the preventive effect of seaweed consumption against breast cancer (Teas, 1983;Kang et al, 2004).…”
Section: Fiber Intake Pattern S Fukuda Et Almentioning
confidence: 99%
“…Michel et al (1996) reported that the characteristic fermentation pattern associated with the fiber from the three brown algae they investigated was attributable to the peculiar fermentation of alginates, and mannuronate was shown not to be directly involved. As for the relationship of seaweed consumption to carcinogenesis, several reports have shown preventive effects of seaweeds against colorectal carcinogenesis in epidemiological studies (Tokudome et al, 1991;Hoshiyama et al, 1993), or in experimental studies in rats (Yamamoto and Maruyama, 1985;Teas et al, 1998); proposed mechanisms for such effects include inhibition of reactive oxygen species (Maruyama et al, 2003;Suzuki et al, 2004), or the modulation of natural killer cell activity (Teas, 1983). Furthermore, there are several reports regarding the preventive effect of seaweed consumption against breast cancer (Teas, 1983;Kang et al, 2004).…”
Section: Fiber Intake Pattern S Fukuda Et Almentioning
confidence: 99%
“…Sericin nanoparticles, apart from the general advantages of protein nanoparticles, may also offer certain other benefits of the inherent property of sericin. Those include antioxidant [84][85][86][87] and antitumor action [88]; enhancement of the bioavailability of such elements as Zn, Mg, Fe, and Ca [89]; as well as suppression of coagulation when sulfated [90]. Sericin is non-toxic to fibroblast cells.…”
Section: Sericinmentioning
confidence: 99%
“…Specifically, sericin is highly resistant to oxidation (Suzuki et al, 2004), is UV resistant (Sarovart et al, 2003), and has a moisturizing effect on skin (Padamwar et al, 2005). In addition, Tsubouchi et al (2005) reported that sericin improves the attachment of cultured human skin fibroblasts.…”
Section: Introductionmentioning
confidence: 99%